Health behaviour outcomes of a family based intervention for paediatric obesity in primary care: A randomized type II hybrid effectiveness‐implementation trial. Issue 9 (30th March 2021) - Smith, Justin D.; Berkel, Cady; Carroll, Allison J.; Fu, Emily; Grimm, Kevin J.; Mauricio, Anne M.; Rudo‐Stern, Jenna; Winslow, Emily; Dishion, Thomas J.; Jordan, Neil; Atkins, David C.; Narayanan, Shrikanth S.; et al.
Summary: Background: Paediatric obesity is a multifaceted public health problem. Family based behavioural interventions are the recommended approach for the prevention of excess weight gain in children and adolescents, yet few have been tested under "real‐world" conditions. Objectives: To evaluate the effectiveness of a family based intervention, delivered in coordination with paediatric primary care, on child and family health outcomes. Methods: A sample of 240 families with racially and ethnically diverse (86% non‐White) and predominantly low‐income children (49% female) ages 6 to 12 years (M = 9.5 years) with body mass index (BMI) ≥85th percentile for age and gender were identified in paediatric primary care. Participants were randomized to either the Family Check‐Up 4 Health (FCU4Health) program (N = 141) or usual care plus information (N = 99). FCU4Health, an assessment‐driven individually tailored intervention designed to preempt excess weight gain by improving parenting skills was delivered for 6 months in clinic, at home and in the community. Child BMI and body fat were assessed using a bioelectrical impedance scale and caregiver‐reported health behaviours (eg, diet, physical activity and family health routines) were obtained at baseline, 3, 6 and 12 months. Results: Change in child BMI and percent body fat did not differ by group assignment. Path analysis indicated significant group differences in child health behaviours at 12 months, mediated by improved family health routines at 6 months. Conclusion: The FCU4Health, delivered in coordination with paediatric primary care, significantly impacted child and family health behaviours that are associated with the development and maintenance of paediatric obesity. BMI did not significantly differ.